Manejo de las finanzas y costos en la producción y distribución de leche cruda en la Vereda la Esperanza de la ciudad de Duitama. (2023)
In the department of Boyacá, the production of raw milk is an activity that characterizes the region, since, through experience, the producers and distributors of this perishable food have created knowledge that has allowed them to develop their businesses informally in the region. Most of the cases by people characteristic of the region, in this case the peasants.